The impact of simulation applications on the problem-solving and decision-making skills of school administrators and prospective administrators: An experimental study - Atici, Esra Kaya; Turhan, Muhammed (Springer, 2025)
Although the competencies expected from administrators have increased with the development of technology, it is seen that there are a limited number of studies on innovative approaches in training school administrators. The study aims investigate the impact of simulation applications on the problem-solving and decision-making abilities of school administrators and prospective administrators. To achieve this objective, a pretest and posttest quasi-experimental study was conducted, using experimental and control groups. The study employed a parallel mixed design, which combines quantitative and qualitative research approaches. The research group consisted of 61 school administrators and prospective administrators, with 30 participants in the experimental group and 31 in the control group. The Melbourne Decision Making Questionary I-II (MCDS I-II) and the Problem Solving Inventory (PSI) were utilized as data collection instruments before and after the 6-week experimental process. Furthermore, a semi-structured interview form was administered to the experimental group participants following the application. The results of the data analysis indicated that the simulation application effectively enhanced the decision-making and problem-solving skills of the experimental group participants, while reducing the use of approaches that hindered the positive effects of these skills.
Keywords: School administrator training; Simulation; Simulation supported training; Problem-solving skills; Decision making skills